Homobimetallic Complexes of Platinum(II) Group Metals with Sulphur Containing Ligands R2C = CR2 (R = 5-Phenyl-1,3,4-Oxadiazole-2-Thiol; 4,5-Diphenyl-1,2,4-Triazole-3-Thiol or Mercaptobenzothiazole) - J. Al-Hayaly, Lama'an; H. Buttrus, Nabeel; A.K. Al-Allaf, Talal (Asian Journal of Chemistry, 2010)
Homobinuclear complexes of the type [Cl2MR2C=CR2MCl2] [M = Ni(II), Pd(II) or Pt(II) and R = 5-phenyl-1,3,4-oxadiazole-2-thiol; 4,5-diphenyl-1,2,4-triazole-3-thiol or mercaptobenzothiazole], have been prepared by the reaction of newly prepared sulphur containing ligands of the type R2C=CR2 with the appropriate metal salts of Ni(II), Pd(II) or Pt(II). The complexes have been characterized on the basis of their CHN elemental analysis, molar conductivity, room temperature magnetic moment, I.R. and electronic spectra. Octahedral enviroment around Ni(II) while square-planar geometry around Pd(II) or Pt(II) have been deduced on the basis of magnetic and spectral studies.